The ethics of academic research and writing / Luay Thanoon Younis - Younis, Luay Thanoon (Faculty of Dentistry, 2014)
Plagiarism is an act or instance of using or closely imitating the language and thoughts of another author without authorization and the representation of that author's work as one's own without appropriately crediting the original author. This misconduct could be committed recklessly, knowingly, or intentionally.